Biodistribution of Liposome-Encapsulated Bacteriophages and Their Transcytosis During Oral Phage Therapy - Otero, Jennifer; García-Rodríguez, Alba; Cano-Sarabia, Mary; Maspoch, Daniel; Marcos, Ricard; Cortés, Pilar; Llagostera, Montserrat (Frontiers in Microbiology, 2019)
This study sheds light on the biodistribution of orally administered, liposome-encapsulated bacteriophages and their transcytosis through intestinal cell layers. Fluorochrome-labeled bacteriophages were used together with a non-invasive imaging methodology in the in vivo visualization of bacteriophages in the stomach and intestinal tract of mice. In those studies, phage encapsulation resulted in a significant increase of the labeled phages in the mouse stomach, even 6 h after their oral administration, and without a decrease in their concentration. By contrast, the visualization of encapsulated and non-encapsulated phages in the intestine were similar. Our in vivo observations were corroborated by culture methods and ex vivo experiments, which also showed that the percentage of encapsulated phages in the stomach remained constant (50%) compared to the amount of initially administered product. However, the use of conventional microbiological methods, which employ bile salts to break down liposomes, prevented the detection of encapsulated phages in the intestine. The ex vivo data showed a higher concentration of non-encapsulated than encapsulated phages in liver, kidney, and even muscle up to 6 h post-administration. Encapsulated bacteriophages were able to reach the liver, spleen, and muscle, with values of 38% ± 6.3%, 68% ± 8.6%, and 47% ± 7.4%, respectively, which persisted over the course of the experiment. Confocal laser scanning microscopy of an in vitro co-culture of human Caco-2/HT29/Raji-B cells revealed that Vybrant-Dil-stained liposomes containing labeled bacteriophages were preferably embedded in cell membranes. No transcytosis of encapsulated phages was detected in this in vitro model, whereas SYBR-gold-labeled non-encapsulated bacteriophages were able to cross the membrane. Our work demonstrates the prolonged persistence of liposome-encapsulated phages in the stomach and their adherence to the intestinal membrane. These observations could explain the greater long-term efficacy of phage therapy using liposome-encapsulated phages.